2023
DOI: 10.3389/fphar.2023.1240820
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the pharmacological effects and molecular mechanisms of emodin in the treatment of metabolic diseases

Linyuan Yu,
Yongliang Zhao,
Yongli Zhao

Abstract: Rhubarb palmatum L., Polygonum multijiorum Thunb., and Polygonum cuspidatum Sieb. Et Zucc. are traditional Chinese medicines that have been used for thousands of years. They are formulated into various preparations and are widely used. Emodin is a traditional Chinese medicine monomer and the main active ingredient in Rhubarb palmatum L., Polygonum multijiorum Thunb., and Polygonum cuspidatum Sieb. Et Zucc. Modern research shows that it has a variety of pharmacological effects, including promoting lipid and glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 200 publications
0
4
0
Order By: Relevance
“…Once the AMPK, p-ACC, and CPT-1 pathways are activated, fatty acid oxidation occurs [50]. The overexpression of SREBP-1c causes lipogenesis, which is correlated with the FAS genes that synthesize fatty acids [51]. In this study, the ACC in the HF group showed the highest protein expression levels among all groups, but the lowest activating expression levels were found for p-ACC.…”
Section: Discussionmentioning
confidence: 48%
“…Once the AMPK, p-ACC, and CPT-1 pathways are activated, fatty acid oxidation occurs [50]. The overexpression of SREBP-1c causes lipogenesis, which is correlated with the FAS genes that synthesize fatty acids [51]. In this study, the ACC in the HF group showed the highest protein expression levels among all groups, but the lowest activating expression levels were found for p-ACC.…”
Section: Discussionmentioning
confidence: 48%
“…Additionally, emodin has been shown potential as candidate drugs for treating hyperlipidemia by activating the AMPK/SREBP-2/PCSK9/LDLR signaling pathway (He et al, 2022). In diabetes, emodin accelerate wound healing by promoting angiogenesis through the FGFR1/ERK signaling pathway (Yu et al, 2023a). They enhance granulation tissue formation, neovascularization, collagen deposition, and reduce in ammatory cell in ltration, suggesting their potential as topical treatments for diabetic wounds (Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Emodin regulates lipid metabolism and adenosine monophosphate-activated protein kinase, peroxisome proliferator-activated receptors, and nuclear factor kappa B signaling pathways, preventing the development of obesity, hyperlipidemia, nonalcoholic fatty liver disease, diabetes, atherosclerosis, and osteoporosis. 103 Emodin also has anticancer, antiinflammatory, and anti-oxidant potential. 102…”
Section: Emodinmentioning
confidence: 99%